Namibian learners' perceptions regarding English second language writing activities (Journal for Studies in Humanities and Social Sciences, 2017)
Namibian learners exhibit low performance in English creative writing. This might be attributed partly to learners’ attitudes towards the English writing activities as prescribed by the school curriculum. This paper investigated Grade 11 learners’ perceptions of English Second Language (ESL) writing activities at selected schools in Windhoek, Namibia. The study employed a mixed-method design that involved a survey. Purposeful sampling was used to select three schools on the basis of learners’ performance in ESL writing. A total of 286 learners participated in the study. Quantitative data were collected via questionnaires and qualitative date via open-ended questions in the questionnaire and focus group discussions. Findings revealed, amongst others, that learners had both negative and positive attitudes towards ESL writing. When compared, a larger number of learners felt that writing activities were easy; fewer learners regarded them as difficult. The research also revealed differences in how learners enjoyed and regarded the usefulness of the ESL writing activities. Chi-square results in relation to sex demonstrated that in most cases, the differences between boys and girls were not statistically significant. However, a clear difference was found be-tween boys and girls with regard to the writing of diaries. Chi-square analyses done on the schools’ performance level in relation to perceptions of ESL writing activities yielded clear and statistically significant differences between the three schools.